2010
DOI: 10.3390/toxins2071898
|View full text |Cite
|
Sign up to set email alerts
|

The Systemic and Pulmonary Immune Response to Staphylococcal Enterotoxins

Abstract: In response to environmental cues the human pathogen Staphylococcus aureus synthesizes and releases proteinaceous enterotoxins. These enterotoxins are natural etiologic entities of severe food poisoning, toxic shock syndrome, and acute diseases. Staphylococcal enterotoxins are currently listed as Category B Bioterrorism Agents by the Center for Disease Control and Prevention. They are associated with respiratory illnesses, and may contribute to exacerbation of pulmonary disease. This likely stems from the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 126 publications
1
16
0
Order By: Relevance
“…SEB is the superantigen commonly associated with staphylococcal food poisoning, but it can also cause widespread systemic damage and toxic shock syndrome (3,4). The toxin has been shown to cause lethal pulmonary disease and contribute to pneumonia in vivo (5)(6)(7). SEB is stable to aerosolization, and inhalation of small amounts can cause severe lung pathology, shock, and death (4)(5)(6)(7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SEB is the superantigen commonly associated with staphylococcal food poisoning, but it can also cause widespread systemic damage and toxic shock syndrome (3,4). The toxin has been shown to cause lethal pulmonary disease and contribute to pneumonia in vivo (5)(6)(7). SEB is stable to aerosolization, and inhalation of small amounts can cause severe lung pathology, shock, and death (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…The toxin has been shown to cause lethal pulmonary disease and contribute to pneumonia in vivo (5)(6)(7). SEB is stable to aerosolization, and inhalation of small amounts can cause severe lung pathology, shock, and death (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Since these studies on NHP, there is evidence that links SEs exposure to asthma and respiratory problems (Kumar et al, 2010). Inflammatory reactions in the lung are induced by TNF-and two life-threatening syndromes, vascular leak and respiratory distress develop during toxic shock (Aubert et al, 2000;Herz et al, 1999;Neuman et al, 1997).…”
Section: Pulmonary Complicationsmentioning
confidence: 99%
“…TSS pathophysiology involves many intricate extracellular and intracellular signaling pathways and at this time, the exact pathways or pathways responsible for the syndrome are not known (Davis et al, 1980;Kumar et al, 2010;Pinchuk et al, 2010). Hallmark studies during the 1990s showed that the toxicity of SEB was due to massive T-cell proliferation and proinflammatory cytokine production White et al, 1989).…”
Section: Toxic Shock Syndromementioning
confidence: 99%
“…aureus is a round-shaped, facultative anaerobe, which can produce an array of superantigens (SAgs), including staphylococcal exotoxins, enterotoxins, and toxic shock syndrome toxin 1 (TSST-1). These toxins exert their hyper-stimulatory properties and cause food poisoning, toxic shock syndrome, acute lung diseases, and autoimmune diseases [7][8][9][10]. The superantigenicity of SAgs is largely achieved by the activation of APCs and T cells, leading to a massive release of cytokines, including IL-1β, IL-6, and TNFα [11].…”
Section: Staphylococcal Superantigens As Antibody Targetsmentioning
confidence: 99%